THE FUTURE OF ISLAMIC FINANCE AS INCLUSIVE FINANCE: EXPERIENCE FROM COMMUNITY SERVICE IN INDONESIA, MALAYSIA AND THAILAND - Andri Soemitra; Isnaini Harahap; Nurlaila; Fauzi Arif Lubis; Imsar (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
Islamic finance is a global phenomenon that has penetrated various countries, both Muslim-majority countries and non-Muslim-majority countries. The inclusive character of Islamic finance makes it very possible for it to be accepted in various regions. This paper focuses on three countries in Southeast Asia, namely Indonesia, Malaysia and Thailand. The aim of this writing is to understand the latest developments in Islamic finance in these three countries from inclusive financial perspective. This community service paper approach uses literature study. The paper results show that Islamic finance in Indonesia, Malaysia and Thailand shows different degrees. Malaysia can be said to be a leader in the Islamic finance sector not only in Asia but also at the world level. Indonesia shows a strong target to become the world's halal center. Meanwhile, Thailand also does not want to be left behind, especially developing Islamic social finance apart from focusing on the halal tourism industry.